Why do cities in the global South pursue waste incineration rather than source segregation and recycling? Insights from Bangladesh - Akther, Shahana; Evans, James; Millington, Nate (Frontiers in Sustainability, 2024)
Source segregation and recycling of waste are crucial components of sustainable solid waste management. In most global South cities, recycling and segregation are informal. They receive little attention due to lack of political interest and institutional capacity, weak regulatory frameworks and enforcement, lack of economic incentives and low priority in planning. A complex economic system is involved in waste management in the global South, along with an informal sector that collects and recycles valuable materials. Rather than searching for solutions to improve collection and disposal services, this paper uses a political ecology approach to understand how political economy influences and controls municipal solid waste management practices on the ground focusing on source segregation and recycling and how power relations influence how waste is handled, disposed of, and recycled. Dhaka's waste governance regime emphasizes waste-to-energy generation without considering source segregation and recycling. Waste governance wants to benefit from informal waste collection and recycling without integrating them into policy frameworks, even though they have high resource recovery potential. The paper asks why, despite the potential to implement the 3R strategy by source segregation and promote sustainable waste management, the government opted for a centralized mechanical solution (incineration) for handling waste. A case study method was used to collect data by interviewing key stakeholders and conducting field observations between July and September 2022 in Dhaka, Bangladesh. The study examines how politics and political economy affect waste management policy intervention, as well as how it affects waste infrastructure and waste management systems in global South megacities. Effective and sustainable waste management in global South requires an integrated formal and informal approach to enhance source segregation and resource recovery. The study provides an evidence-based understanding of waste management practices, facilitates implementation of 3R strategy, policymaking, and provides additional knowledge for global South megacities facing similar challenges.